Urinary Fractional Clearance of Sodium in 8 Healthy Beagle Dogs Fed Normal, Low, or Ultralow Sodium Diets - R. G. Lobetti (Veterinary Medicine International)
The purpose of this study was to investigate in healthy adult dogs if there was a daily fluctuation in the FCNa, the role that dietary sodium intake played on the FCNa, and the role that feeding played on the obtained value for FCNa. Three different diets were used in a group of 8 healthy beagle dogs in a crossover design. The sodium content of the diets was normal (0.26%), low (0.18%), and ultralow (0.06%). Spot urine and blood samples were collected from which the urine and serum sodium and creatinine concentration were determined, and the FCNa was calculated. The median FCNa for the normal, low, and ultralow sodium diets was 0.5, 0.77, and 0.15, respectively. Individual dogs showed a daily variation in FCNa, and samples which were collected shortly after eating showed the greatest variation. This study showed that in a group of healthy beagle dogs without obvious renal disease, the FCNa could exceed 1 and that there was both an individual and daily variation in the FCNa. The greatest variation was seen whilst the dogs were fed the low and ultralow sodium diets and when the samples were collected shortly after eating. This study concluded that an FCNa > 1% may not be indicative of acute tubular dysfunction in young dogs, and use of the FCNa for assessing renal function in clinical cases should take into account the animal’s diet, as well as the time the samples were taken in relation to feeding.